IMMU-24. PD-1/PD-L PATHWAY IS ASSOCIATED WITH TWO CELL PATTERN FORMATION IN INTRACRANIAL GERMINOMA. (6th November 2017) - Arakawa, Yoshiki; Liu, Bin; Yokogawa, Ryuta; Tokunaga, Shinya; Hattori, Etsuko; Fukui, Nobuyuki; Terada, Yukinori; Matsui, Yasuzumi; Tannji, Masahiro; Mineharu, Yohei; Miyamoto, Susumu
Abstract: BACKGROUND: Intracranial germinoma has two cell pattern with large undifferentiated tumor cell and tumor infiltrating lymphocytes (TILs) but the meaning of this phenotype has not been known. Recently, PD-1/PD-L pathway has been recognized to work as anti-tumor immune system. In this study, we evaluated a relationship between TILs and PD-1/PD-L pathway in intracranial germinoma. METHODS: In formalin-fixed, paraffin-embedded tumor specimens from 25 patients with intracranial germinomas, we immunohistochemically analyzed the expressions of PD-L1/2 in tumor cells and TILs with PD-1, CD3+, CD8+, CD4+, Foxp3+. Statistical analysis was performed these expressions and clinical data. RESULTS: PD-1 expression in TILs was detected in 76% (19/25). PD-L1 and PD-L2 expression in tumor cells were detected in 96% (24/25) and 84% (21/25), respectively. High expression of PD-1 was inclined to increase CD3+ TILS. Expression of PD-1 was correlated with Foxp3+ TILs density, CD8+ TILs density, but not with CD4+ TILs density. Furthermore, expression of PD-1 is strongly correlated with Foxp3+/CD4+ ratio in TILs. CONCLUSION: The increase of PD-1+ TILs induces immune dysfunction of CD8+ TILs. The induction of Foxp3+ TILs from CD4+TILs causes immune tolerance. These observations indicate that the breakdown of anti-tumor immune system may be associated with two cell pattern formation as well as oncogenesis in intracranial germinoma.